Efficacy of Yoga Interventions in Alleviating Physician Burnout: A Review of Randomized Controlled Trials - Giridharan, Selvaraj; Ziff, Charlotte (International Research Journal of Ayurveda & Yoga, 2024)
Background: Physician burnout has become a significant concern in the medical community. It is characterized by emotional exhaustion, depersonalization, and a reduced sense of personal accomplishment. Considering physicians’ unique challenges, there is an increasing interest in exploring holistic interventions such as yoga, which may benefit stress management and overall well-being. Methods: We conducted a comprehensive analysis of randomised controlled trials published between 2014 and 2023, assessing the impact of yoga interventions on physician burnout across various databases. Results: Our analysis uncovered five randomized trials demonstrating that yoga can effectively alleviate symptoms of physician burnout, such as depersonalization and emotional exhaustion. Furthermore, yoga has been shown to improve professional fulfillment, flexibility, and overall well-being. These advantages extend beyond stress relief and encompass various aspects of professional life. Conclusion: Yoga interventions can alleviate physician burnout by targeting physical, emotional, and mental health factors. According to the findings, incorporating yoga-based wellness programs in health-care settings can promote physician well-being, enhance job satisfaction, and improve patient care. Additional research is required to strengthen the evidence base and facilitate the implementation of customized yoga interventions in the medical profession. Burnout is a well-established occupational syndrome with significant implications for various professions, particularly in the medical field.[1] It is a complex phenomenon characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment due to chronic occupational stress.[2] While burnout is not officially classified as a medical condition, it has been linked to mental illness and can have severe consequences for individuals and organizations. It is a multidimensional occupational phenomenon that can affect individuals in various contexts, as demonstrated by studies on parental burnout and burnout among university students during the COVID-19 pandemic.[3-5]